2024
DOI: 10.1186/s12875-023-02249-5
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of a reconfigured domestic violence and abuse training and support intervention responding to affected women, men, children and young people through primary care

Eszter Szilassy,
Caroline Coope,
Elizabeth Emsley
et al.

Abstract: Background Identification in UK general practice of women affected by domestic violence and abuse (DVA) is increasing, but men and children/young people (CYP) are rarely identified and referred for specialist support. To address this gap, we collaborated with IRISi (UK social enterprise) to strengthen elements of the IRIS + intervention which included the identification of men, direct engagement with CYP, and improved guidance on responding to information received from other agencies. IRIS + wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The IRIS+ pilot study showed feasibility and acceptability of the intervention to clinicians and those affected by DVA. 17 18 The aim of this study was to evaluate the prospective cost-effectiveness of the IRIS+ intervention when compared with usual care (the IRIS intervention). This study addresses a gap in the literature around the possible cost-effectiveness of interventions targeting men and children as well as women experiencing DVA.…”
Section: Introductionmentioning
confidence: 99%
“…The IRIS+ pilot study showed feasibility and acceptability of the intervention to clinicians and those affected by DVA. 17 18 The aim of this study was to evaluate the prospective cost-effectiveness of the IRIS+ intervention when compared with usual care (the IRIS intervention). This study addresses a gap in the literature around the possible cost-effectiveness of interventions targeting men and children as well as women experiencing DVA.…”
Section: Introductionmentioning
confidence: 99%